PERAN GURU DALAM PEMBIASAAN BERBAHASA INDONESIA UNTUK MENINGKATKAN KOGNITIF SISWA DI SDN 02 KARANGTUMARITIS INDRAMAYU JAWA BARAT - Annisa Mardiah; Anggi Fitri Hasanah; Diah Laila Wulan; Fauziah Syania Asri; Dewi Nopasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the role of teachers in Indonesian language habituation as an effort to improve students' cognitive abilities in schools. There are significant challenges in accustoming students to using Indonesian due to the dominant use of regional languages ​​in their daily lives. This condition has the potential to hinder the development of students' cognitive abilities, which are closely related to language mastery. The main objective of this study is to describe the strategies implemented by teachers and identify the impact of Indonesian language habituation on students' cognitive development. This study uses a qualitative approach with descriptive methods. Data were collected through direct observation, in-depth interviews with teachers and students, and documentation studies related to school programs. The results indicate that teachers play a central role in the success of this habituation program. Teachers employ various strategies, such as consistently using Indonesian when communicating with students, implementing interactive and enjoyable learning methods, and integrating Indonesian into every subject. These practices positively impact students' cognitive abilities, as evidenced by their ability to understand lesson concepts, reason, and construct sentences in a more structured and logical manner. Thus, teachers' active role and creative strategies have proven effective in addressing language learning challenges and contributing significantly to students' cognitive development. Keywords: Teacher Role, Language Habits, Student Cognitive